Hematopoietic Stem Cell Transplantation in People With Active Secondary Progressive Multiple Sclerosis. (14th March 2023) - Boffa, Giacomo; Signori, Alessio; Massacesi, Luca; Mariottini, Alice; Sbragia, Elvira; Cottone, Salvatore; Amato, Maria Pia; Gasperini, Claudio; Moiola, Lucia; Meletti, Stefano; Repice, Anna Maria; Brescia Morra, Vincenzo; et al.
Abstract : Background and Objectives: Uncontrolled evidence suggests that autologous hematopoietic stem cell transplantation (AHSCT) can be effective in people with active secondary progressive multiple sclerosis (SPMS). In this study, we compared the effect of AHSCT with that of other anti-inflammatory disease-modifying therapies (DMTs) on long-term disability worsening in active SPMS. Methods: We collected data from the Italian Bone Marrow Transplantation Study Group and the Italian Multiple Sclerosis Register. Patients were considered eligible if treatment had been started after the diagnosis of SPMS. Disability worsening was assessed by the cumulative proportion of patients with a 6-month confirmed disability progression (CDP) according to the Expanded Disability Status Scale (EDSS) score. Key secondary endpoints were the EDSS time trend after treatment start and the prevalence of disability improvement over time. Time to first CDP was assessed by means of proportional hazard Cox regression models. A linear mixed model with a time × treatment group interaction was used to assess the longitudinal EDSS time trends. Prevalence of improvement was estimated using a modified Kaplan-Meier estimator and compared between groups by bootstrapping the area under the curve. Results: Seventy-nine AHSCT-treated patients and 1975 patients treated with other DMTs (beta interferons, azathioprine, glatiramer-acetate, mitoxantrone, fingolimod, natalizumab, methotrexate, teriflunomide, cyclophosphamide, dimethyl fumarate, and alemtuzumab) were matched to reduce treatment selection bias using propensity score and overlap weighting approaches. Time to first CDP was significantly longer in transplanted patients (hazard ratio [HR] = 0.50; 95% CI = 0.31–0.81; p = 0.005), with 61.7% of transplanted patients free from CPD at 5 years. Accordingly, EDSS time trend over 10 years was higher in patients treated with other DMTs than in AHSCT-treated patients (+0.157 EDSS points per year compared with −0.013 EDSS points per year; interaction p < 0.001). Patients who underwent AHSCT were more likely to experience a sustained disability improvement: 34.7% of patients maintained an improvement (a lower EDSS than baseline) 3 years after transplant vs 4.6% of patients treated by other DMTs ( p < 0.001). Discussion: The use of AHSCT in people with active SPMS is associated with a slowing of disability progression and a higher likelihood of disability improvement compared with standard immunotherapy. Classification of Evidence: This study provides Class III evidence that autologous hematopoietic stem cell transplants prolonged the time to CDP compared with other DMTs.